Integration of Philosophy in the Implementation of Islamic Education Management from the Perspective of the Quran - Ramadhina, Marini Shadrina; Wardhana, Kautsar Eka (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
In the face of various challenges stemming from the advancement of science and specialization across disciplines, the continual evolution of knowledge endures, seamlessly transitioning from one era to the next. The progression of knowledge development would be rendered impossible without human involvement or capability. The Qur'an provides guidance and ethical teachings that hold the potential for seamless integration into the decision-making processes, strategic planning, and governance of educational institutions. Delving deeper into the integration of philosophy into the management of Islamic education becomes imperative to gauge the depth of comprehension through the lens of the Qur'an. This research uses qualitative methods, examining Quranic verses related to integrating philosophy into Islamic educational management. By means of a thorough literature review and an exploration of pivotal Qur'anic verses, encompassing Surah Al-Jasiyah verse 20, Surah Al-Qamar verse 17, Al-Baqarah verse 2, Surah Yunus verse 3, Surah Al-Ra’du verse 2, Surah Al-A’raf verse 29, Surah Al-Ahzab verse 24, Surah An-Nisa verse 58, Surah Ar-Rahman verses 7-9, Surah Al-Baqarah verse 286, Surah Al-Hasyr verse 18, Surah Ali Imran verse 103, Surah Al-Kahf verse 2, Surah Hud verse 117, and Surah Ash-Shura verse 6, the research findings lead to the conclusion that the philosophical underpinning in the management of Islamic education, when harmoniously integrated from the perspective of the Qur'an, can give rise to a comprehensive and all-encompassing approach.